STATUS HUKUM DAN PERLINDUNGAN ENVIRONMENTALLY DISPLACED PERSONS DITINJAU DARI KONVENSI 1951 TENTANG STATUS PENGUNGSI - Yuthi Sinari; Suhaidi Suhaidi; Jelly Leviza (Journal of USU International Law, 2013)
AbstractClimate change and exacerbating global warming in the recent few decades have triggered an urgent effect that threatens the lives of millions of people. The number of persons seeking refugee protection due to environmental degradation has increased to 25 million people, prominently preceding other groups of people. The preponderance of contemporary human outpouring consists of persons seeking to escape the deteriorating environments of developing countries, but the surge in environmental refugees will soon outpace the ability of the developing world to cope with them. Developed countries will soon feel the effects of this problem. No host country will be able to escape the effects of the growing numbers of environmental refugees for much longer. This heartbreaking phenomenon will remain a unique tragedy in the history of human beings. Forced migration due to environmental degradation has inevitably pervaded every aspect of life. The only solution to overcome hostile environment migration is to intensify international cooperation and corroborate burden-sharing principle. Furthermore, international conventions and declarations have been created to expand the definition of refugees embodied in Article 1 of the 1951 Convention Relating to Refugee Status to include environmentally displaced persons and optimize the international protection for refugees.Keyword: Refugees, Environmentally Displaced Persons